2015
DOI: 10.1002/eco.1658
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall infiltration and soil hydrological characteristics below ancient forest, planted forest and grassland in a temperate northern climate

Abstract: How rainfall infiltration rate and soil hydrological characteristics develop over time under forests of different ages in temperate regions is poorly understood. In this study, infiltration rate and soil hydrological characteristics were investigated under forests of different ages and under grassland. Soil hydraulic characteristics were measured at different scales under a 250-year-old grazed grassland (GL), 6-year-old (6yr) and 48-year-old (48yr) Scots pine (Pinus sylvestris) plantations, remnant 300-year-ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 63 publications
6
41
2
3
Order By: Relevance
“…The researchers found that the field hydraulic conductivity of top 0.04-0.15 m (0.88-25.60 cm/hr) was larger than 0.15-0.25 m (0.30-2.30 cm/hr) depth. The current study observed less variability in infiltration rate with depth compared with Archer's et al (2016) study.…”
Section: Anova Test Results For Growing/nongrowing Seasonal Effect On contrasting
confidence: 69%
“…The researchers found that the field hydraulic conductivity of top 0.04-0.15 m (0.88-25.60 cm/hr) was larger than 0.15-0.25 m (0.30-2.30 cm/hr) depth. The current study observed less variability in infiltration rate with depth compared with Archer's et al (2016) study.…”
Section: Anova Test Results For Growing/nongrowing Seasonal Effect On contrasting
confidence: 69%
“…Research has shown that soils under long undisturbed broadleaf woodland (180 and 500 years‐old) have higher saturated hydraulic conductivities and macroporosity than more recently established woodland (45 years‐old) or improved pasture, where no difference was observed (Archer et al ., ). Other studies have noted this contrast between old forests versus those established in recent decades (Hümann et al ., ; Archer et al ., ), although in some instances trees may negatively influence soil infiltration (Chandler and Chappell, ). Reported increases in soil hydraulic conductivity also occurred in areas recently planted with trees and excluding livestock relative to grazed improved pasture (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…For different land cover types, soil moisture is higher in areas with vegetation than in the bare land. This is because vegetation can preserve soil moisture, especially in arid ecosystems [52]. The vegetation patches can retain runoff and make it infiltrate into the soil.…”
Section: Discussionmentioning
confidence: 99%